Pengaruh Relative Advantage dan Compatibility Terhadap Adopsi Qris pada Usaha Mikro dan Kecil Kabupaten Karawang - Abdul Yusuf; Tiar Lina Situngkir; Rabhi Fathan; Ridho Fadilah Yuslen (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research uses quantitative methods with descriptive and verification approaches. The population in this research is Karawang Regency Micro and Small Bussines. Based on Isaac and Michael's calculations, the sample for this study was 383 respondents. The sampling method used in this research is simple random sampling. This research uses range-of-scale analysis techniques and SEM-PLS with Smart PLS and Microsoft Excel tools. The results of the research show that there is a partial influence of Relative Advantage and Compatibility on Adoption, namely 31.7% and 29%.